2017
DOI: 10.1002/etc.3693
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxicity of arsenic during Rhinella arenarum embryonic and larval development: Potential biomarkers of oxidative stress and antioxidant response

Abstract: The Argentinean autochthonous toad Rhinella arenarum was selected to study the chronic toxicity of arsenic (As) and the biochemical responses elicited by exposure to As in water during embryonic and larval development. Significant decreases in the total reactive antioxidant potential and in catalase activity were observed in individuals exposed chronically to sublethal concentrations of As, which is indicative of an oxidative stress situation. However, an antioxidant response was elicited during chronic exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In our experience, the antioxidant enzymatic activity response varies greatly in R. arenarum embryos and larvae exposed to OP pesticides, showing cycles of induction followed by inhibition attributed to catalytic site inactivation due to ROS attack 8, 24,35,41,43 . In the response of R. arenarum larvae to arsenic-induced oxidative stress, we observed an increase in Cu/Zn SOD protein, followed by a decrease together with a decrease in CAT protein, with similar enzymatic activity patterns 11,44 .…”
Section: Ma Et Al (2018)mentioning
confidence: 52%
See 1 more Smart Citation
“…In our experience, the antioxidant enzymatic activity response varies greatly in R. arenarum embryos and larvae exposed to OP pesticides, showing cycles of induction followed by inhibition attributed to catalytic site inactivation due to ROS attack 8, 24,35,41,43 . In the response of R. arenarum larvae to arsenic-induced oxidative stress, we observed an increase in Cu/Zn SOD protein, followed by a decrease together with a decrease in CAT protein, with similar enzymatic activity patterns 11,44 .…”
Section: Ma Et Al (2018)mentioning
confidence: 52%
“…Finally, remarking on the complexity of the responses and crosstalk between pathways, we have reported for different developmental states in R. arenarum and cell cultures exposed to CPF, other OP pesticides or arsenic, an increase in MEK1/2 and ERK1/2 proteins, their translocation to the nucleus, and ERK phosphorylation, considering that the MAP kinase pathway regulates the Nrf2-mediated response. Additionally, cFOS and cJUN proteins are increased after oxidative stress in R. arenarum embryos and larvae 43,44,54 .…”
Section: Ma Et Al (2018)mentioning
confidence: 98%
“…The enhanced translocation of Mek to the nucleus due to CPF exposure might be a stress response downregulating the pathway. Furthermore, cFos and cJun proteins are increased after oxidative stress in R. arenarum embryos and larvae 12 , 47 , 52 . The complex nature of the regulatory crosstalk leading to the prevailing downregulation of biochemical responses in R. arenarum larvae exposed to OP, is depicted in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Generally, the activity of these enzymes is increased after acute exposure to low As concentrations, whereas it is decreased under chronic exposure (Flora, 2011). Several studies have reported As‐induced antioxidant imbalance in freshwater animals (Allen & Rana, 2004; Mardirosian et al, 2016; Sarkar et al, 2014; Tuulaikhuu et al, 2015). These studies demonstrated that some enzymatic and non‐enzymatic factors help in protecting cells by scavenging and clearing ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Gambusia holbrooki chronically exposed to 120 µg/L of As showed increase in the activity of SOD and GR after 9 days and of GST after 55 days of exposure (Tuulaikhuu et al, 2015). In Rhinella arenarun tadpoles, As induced an increase in oxidative stress enzymes, mainly GST, and in gene expression and transcription factors (Mardirosian et al, 2016).…”
Section: Discussionmentioning
confidence: 99%